Localization of Phonological and Semantic Contributions to Reading - Dickens, J. Vivian (J Neurosci, 2019)
Reading involves the rapid extraction of sound and meaning from print through a cooperative division of labor between phonological and lexical–semantic processes. Whereas lesion studies of patients with stereotyped acquired reading deficits contributed to the notion of a dissociation between phonological and lexical–semantic reading, the neuroanatomical basis for effects of lexicality (word vs pseudoword), orthographic regularity (regular vs irregular spelling–sound correspondences), and concreteness (concrete vs abstract meaning) on reading is underspecified, particularly outside the context of strong behavioral dissociations. Support vector regression lesion–symptom mapping (LSM) of 73 left hemisphere stroke survivors (male and female human subjects) not preselected for stereotyped dissociations revealed the differential contributions of specific cortical regions to reading pseudowords (ventral precentral gyrus), regular words (planum temporale, supramarginal gyrus, ventral precentral and postcentral gyrus, and insula), and concrete words (pars orbitalis and pars triangularis). Consistent with the primary systems view of reading being parasitic on language-general circuitry, our multivariate LSM analyses revealed that phonological decoding depends on perisylvian areas subserving sound–motor integration and that semantic effects on reading depend on frontal cortex subserving control over concrete semantic representations that aid phonological access from print. As the first study to localize the differential cortical contributions to reading pseudowords, regular words, and concrete words in stroke survivors with variable reading abilities, our results provide important information on the neurobiological basis of reading and highlight the insights attainable through multivariate, process-based approaches to alexia. SIGNIFICANCE STATEMENT Whereas fMRI evidence for neuroanatomical dissociations between phonological and lexical–semantic reading is abundant, evidence from modern lesion studies establishing the differential contributions of specific brain regions to specific reading processes is lacking. Our application of multivariate lesion–symptom mapping revealed that effects of lexicality, orthographic regularity, and concreteness on reading differentially depend on areas subserving auditory–motor integration and semantic control. Phonological decoding of print relies on a dorsal perisylvian network supporting auditory and articulatory representations, with unfamiliar words relying especially on articulatory mapping. In tandem with this dorsal decoding system, anterior inferior frontal gyrus may coordinate control over concrete semantic representations that support mapping of print to sound, which is a novel potential mechanism for semantic influences on reading.